Surah Al-Kafirun: Tinjauan Stilistika Al-Qur’an - Arbaini, Hanis Rahmah (Universitas Muhammadiyah Gorontalo, 2023)
The Qur'an is a holy book which is still being studied continuously because it is full of aesthetic elements. Along with the many studies of the style of the Al-Quran, new theories have emerged as a tool for analyzing the style of the language of the Qur'an, one of which is stylistics which is able to explain the relationship between language and artistic function and meaning, especially from the phenomenon of deviation and language preference. The object of study in this study focuses on the 109th surah in the Qur'an, namely Al-Kafirun. This study aims to analyze surah Al-Kafirun based on five domain levels or what is called khomsah mustawayat fii 'Ilm al-Uslub namely al-mustawâ al-ṣauti (phonological level), al-mustawâ al-ṣarfi (morphological level), al-mustawâ al-nahwi au al-tarkîbî (syntactic level), al-mustawâ al-dalali (semantic level), and al-mustawâ al-taṣwiri (imagery level). This research uses descriptive-qualitative method and bibliography method.